Combined multiplex loop‐mediated isothermal amplification with lateral flow assay to detect sea and seb genes of enterotoxic Staphylococcus aureus. (1st July 2016) - Yin, H.Y.; Fang, T.J.; Wen, H.W.
Abstract: Staphylococcal enterotoxins (SEs) are the most common cause of food poisoning worldwide and can induce symptoms, such as diarrhoea, vomiting and abdominal cramping. Thus, the aim of this study is to develop a multiplex loop‐mediated isothermal amplification combined with a lateral flow assay (m‐LAMP/LFA) to simultaneously detect the sea and seb genes of Staphylococcus aureus . The amplicons of the sea gene were labelled with digoxigenin (Dig) and biotin while those of seb gene were labelled with fluorescein isothiocyanate (FITC) and biotin. These amplicons were detected using a multiplex LFA with NeutrAvidin‐tagged gold nanoparticles as the detection reagent. After optimization, the detection limit of this assay was 10 2 CFU ml −1   Staph. aureus, which was one tenth that of a multiplex PCR. This assay did not exhibit any cross‐reactivity in detecting other enterotoxic Staph. aureus strains or other food pathogens. After 6 h of enrichment, this developed assay detected 1 CFU ml −1 of Staph. aureus in milk, apple juice, cheese and rice. The developed m‐LAMP/LFA method does not require expensive equipment and can be completely implemented within an 8‐h workday. Therefore, this method can provide an effective means of quickly screening staphylococcal enterotoxin A‐ and/or staphylococcal enterotoxin B‐producing Staph. aureus in food samples. Significance and Impact of the Study: Staphylococcus aureus is one of the major foodborne pathogens worldwide, and its staphylococcal enterotoxin A and B are strongly associated with food poisoning. This work developed a multiplex loop‐mediated isothermal amplification combined with a lateral flow assay (m‐LAMP/LFA) to simultaneously detect the sea and seb genes of Staph. aureus in food samples. The assay has good specificity and sensitivity with ease‐of‐use features, making it ideal for on‐site detection.